The Rhetorical Rhythm In The Diwan "djaddid Khlayak" By The Poet Nacer Lohichi - mouhoubi, samira; rebbani, ourida (El Omda in Linguistics and Discourse Analysis, 2025)
This article also focuses on highlighting the links between sound and meaning in these rhetorical issues and their rhythms, which constitute for the recipient musical sensations that appeal to his hearing and palatable understanding, in a descriptive and analytical study in order to reach the aesthetics of rhetorical rhythm.